Organizational culture on employees ethical behavior within an organization - Hussain, Syed Shah Ibrahim (2019)
The following research study is to understand the construct of organization ethics within the organization as well as to identify and understand the various factors within the organization that influence ethical behavior within the organization. In order to do so, two main independent variables that have been chosen for the research study are the aspect of organizational leadership and the aspect of organizational culture and the study involved undertaking secondary and primary research to understand how the aspects of leadership and culture influences ethical behavior of employees within the organization. The roles of the seniors and the management as well as certain key aspects associated with the organizational culture were evaluated to determine the degree of influence that it had upon ethical employee behavior and conduct.